1998
DOI: 10.1094/pdis.1998.82.3.322
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chitin and Chitosan on the Incidence and Severity of Fusarium Yellows of Celery

Abstract: The effects of chitin and chitosan on disease incidence and severity of Fusarium yellows of celery and on populations of Fusarium oxysporum were investigated between 1994 and 1996. Field experiments were conducted at two locations with a history of severe Fusarium yellows. Disease incidence and severity were significantly reduced by pre-plant chitin amendments to soil. Chitosan applied as a root dip alone did not reduce disease incidence but significantly (P < 0.05) reduced disease severity when used with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(58 citation statements)
references
References 28 publications
2
54
0
2
Order By: Relevance
“…Soil amendment with chitosan has repeatedly been shown to control fungal diseases in numerous crops, especially Fusarium wilts [31][32][33] and grey mould [34,35]. It is also of note that these studies show chitosan to be fungistatic against both biotrophic and necrotrophic pathogens.…”
Section: Effectiveness Of Chitin-based Treatments Against Fungal Pathmentioning
confidence: 95%
“…Soil amendment with chitosan has repeatedly been shown to control fungal diseases in numerous crops, especially Fusarium wilts [31][32][33] and grey mould [34,35]. It is also of note that these studies show chitosan to be fungistatic against both biotrophic and necrotrophic pathogens.…”
Section: Effectiveness Of Chitin-based Treatments Against Fungal Pathmentioning
confidence: 95%
“…Chitin-supplemented application of Stenotrophomonas maltophilia C3 improved the control of bean rust (38) and leaf spot of Festuca arundinacea (40) compared with that of strain C3 alone. Chitin-supplemented application of chitinolytic bacteria has also been proved effective in control of other foliar diseases including early leaf spot of peanut (22) and soilborne diseases (3,17). Phyllobacteria can modify their environment to enhance their colonization of plants by increasing local nutrient concentrations or by producing a layer of extracellular polysaccharides either on the surface of leaves or in the interior (2).…”
mentioning
confidence: 99%
“…According to Deacon (1991), P. oligandrum demonstrates a destructive and parasitic character to many pathogenic fungi. Bell et al (1998), Pięta et al (2006, Nawrocki and Mazur (2007) confirmed the efficiency of chitosan in vegetable protection. The results of the investigations conducted by the above-mentioned authors showed that the protective efficiency of chitosan applied as a means of prevention is clearly better than when applied as a means of intervention.…”
Section: Resultsmentioning
confidence: 92%
“…Mycoparasite Pythium oligandrum, a biologically active substance of the biopreparation Polyversum, belongs to the mentioned antagonistic organisms (Benhamou et al 1997). Moreover, the application of chitosan as protection for many plants against diseases, especially as an immunity inducer for the plants, is highly promising (Lafontaine and Benhamou 1996, Bell et al 1998, Orlikowski et al 2002, Pięta et al 2006, Nawrocki and Mazur 2007.…”
Section: Introductionmentioning
confidence: 99%